2023
DOI: 10.3390/nu15040910
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of Alcoholic Strength: Does It Matter for Public Health?

Abstract: In this work, reduction of alcoholic strength was discussed as a means to reduce consumption and alcohol-attributable harm. Statistical modelling was conducted to (1) estimate its potential for the largest six Western and Central European countries (France, Germany, Italy, Poland, Spain, UK); (2) calculate the increase in taxation necessary to reach this potential, and (3) estimate the mortality gains achieved with the introduction of no- or low-alcohol beverages in the UK and Spain. The high public health pot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 28 publications
(45 reference statements)
0
3
0
Order By: Relevance
“…Rehm et al undertook a modeling study to estimate the population-level health impact achieved by the current introduction of no- or low-alcohol beverages in Great Britain and Spain, and the impact of reducing the ABV of all alcohol products by a relative 10% amongst France, Germany, Italy, Poland, Spain, and United Kingdom [ 7 ]. They found that the current introduction of no- or low-alcohol beverages in Great Britain and Spain is associated with reductions in overall mortality, but to such a small extent that the reductions at a population level were, to any extent, irrelevant; this is because the consumption of no-alcohol products, although increasing, is only a very small proportion of the volume of consumption of all alcohol products [ 1 ].…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Rehm et al undertook a modeling study to estimate the population-level health impact achieved by the current introduction of no- or low-alcohol beverages in Great Britain and Spain, and the impact of reducing the ABV of all alcohol products by a relative 10% amongst France, Germany, Italy, Poland, Spain, and United Kingdom [ 7 ]. They found that the current introduction of no- or low-alcohol beverages in Great Britain and Spain is associated with reductions in overall mortality, but to such a small extent that the reductions at a population level were, to any extent, irrelevant; this is because the consumption of no-alcohol products, although increasing, is only a very small proportion of the volume of consumption of all alcohol products [ 1 ].…”
mentioning
confidence: 99%
“…They found that the current introduction of no- or low-alcohol beverages in Great Britain and Spain is associated with reductions in overall mortality, but to such a small extent that the reductions at a population level were, to any extent, irrelevant; this is because the consumption of no-alcohol products, although increasing, is only a very small proportion of the volume of consumption of all alcohol products [ 1 ]. On the other hand, a relative 10% reduction in the ABV of all alcohol products could have an important population-level impact, reducing overall mortality with a range between 0.42% and 1.26% of all deaths, dependent on the country and whether the consumers are women or men [ 7 ].…”
mentioning
confidence: 99%
See 1 more Smart Citation